Integrated UPLC-HRMS, chemometric tools, and metabolomic analysis of forage palm (Opuntia spp. and Nopalea spp.) to define biomarkers associated with non-susceptibility to Carmine Cochineal (Dactylopius opuntiae) - Matos, Thiago Kelvin Brito (2021)
Metabolomics, together with analytical methods and chemometric tools, point to new paths for selecting species that are resistant to pests and diseases. In this work, the forage palm species’ metabolomic profile was investigated, and the relation between the chemical composition and resistance to Dactylopius opuntiae (carmine cochineal). The study was performed in cladodes of different non-susceptible cultivars (Nopalea cochenillifera (L.) Salm-Dyck, Opuntia stricta (Haw.), Nopalea cochenillifera and susceptible cultivar (Opuntia ficus-indica (L.) Mill.)). Metabolic profile showed 28 metabolites detected in the four species. From these total, 18 metabolites were annotated using UPLC-QTOF-MSE (ultra-performance liquid chromatography coupled with an electrospray ionization quadrupole time-of-flight mass spectrometry operating in MSE mode). By comparing the chemical profiles of non-susceptible and susceptible species through the application of chemometric tools, it was possible to obtain biomarkers (quercetin-3-O-2’,6’-dirhamnosylglucoside, quercetin rhamnosyl dihexoside, and isorhamnetin-3-sophoroside-7-rhamnoside) that may be associated with resistance to carmine cochineal. Metabolomics based on UPLC-QTOF-MSE and chemometric allowed to establish the biomarkers knowledge of the resistance present in forage palm species. These results contribute to developing the initial understanding of flavonoids’ role in the defense mechanisms of cactaceans and can be useful for application in breeding programs; it can increase the chances of success in creating new varieties of plants not susceptible to carmine cochineal.